Managing Highly Resorbed Mandibular Ridges with Combination of Neutral Zone and Different Impression Techniques – A Case Series - Sonam Chauhan; Rajeev Gupta; Mamata Mahajan; Neesha Kumari; Parul Minhas (Indian Journal of Dental Sciences)
A lot of methods and techniques have been suggested for the management of highly resorbed mandibular ridges, neutral zone being one of them which aids in achieving a comparatively stable prosthesis. Now since, recording the anatomy in such cases is one of a challenge, use of special impression techniques proves to be beneficial in such scenarios. This paper presents using neutral zone technique along with special impression techniques to deal with the issue of unstable lower dentures with patients due to extreme ridge resorption.